2017
DOI: 10.1111/ina.12408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine, fine, and black carbon particle concentrations in California child-care facilities

Abstract: Although many U.S. children spend time in child care, little information exists on exposures to airborne particulate matter (PM) in this environment, even though PM may be associated with asthma and other respiratory illness, which is a key concern for young children. To address this data gap, we measured ultrafine particles (UFP), PM 2.5 , PM 10 , and black carbon in 40 California child-care facilities and examined associations with potential determinants. We also tested a low-cost optical particle measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
(80 reference statements)
2
12
0
Order By: Relevance
“…Regarding levels found in schools (Figure ), Buonanno et al and Morawska et al observed the highest concentrations (ranges of 1.95‐3.49·10 4 part/cm 3 and 10.70‐14.00.10 4 part/cm 3 ), respectively, depending on the location of the school; values were higher in trafficked areas than in rural zones and also higher outdoors than indoors. Fonseca et al, both of the studies by Rufo et al and Slezakova et al measured concentrations of between 1.15 and 1.82·10 4 part/cm 3 inside Portuguese schools, which are values that are similar to the measurements of both studies conducted in Greece (between 0.5 and 2.5.10 4 part/cm 3 , and 2.4·10 4 part/cm 3 , respectively) and those found in Australia, Spain, Italy, California, and Seoul, between 0.8·10 4 part/cm 3 and 1.8·10 4 part/cm 3 . Mullen et al, Rufo et al, Weichental et al and Zhang and Zhu quantified the lowest concentrations (between 0.1 and 0.7·10 4 part/cm 3 ).…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Regarding levels found in schools (Figure ), Buonanno et al and Morawska et al observed the highest concentrations (ranges of 1.95‐3.49·10 4 part/cm 3 and 10.70‐14.00.10 4 part/cm 3 ), respectively, depending on the location of the school; values were higher in trafficked areas than in rural zones and also higher outdoors than indoors. Fonseca et al, both of the studies by Rufo et al and Slezakova et al measured concentrations of between 1.15 and 1.82·10 4 part/cm 3 inside Portuguese schools, which are values that are similar to the measurements of both studies conducted in Greece (between 0.5 and 2.5.10 4 part/cm 3 , and 2.4·10 4 part/cm 3 , respectively) and those found in Australia, Spain, Italy, California, and Seoul, between 0.8·10 4 part/cm 3 and 1.8·10 4 part/cm 3 . Mullen et al, Rufo et al, Weichental et al and Zhang and Zhu quantified the lowest concentrations (between 0.1 and 0.7·10 4 part/cm 3 ).…”
Section: Resultssupporting
confidence: 70%
“…Of the 32 articles that fulfilled our criteria, 22 quantified UFP levels in children's specific microenvironments (Table ; Figure and ), while the other 10 studies that were selected measured children's personal exposure to UFP by means of active samplers carried by children (Table ; Figure ). Among the studies regarding microenvironment exposures, 18 (82%) referred to UFP levels in schools or nurseries, 3 referred to transport (2 to schools and 1 to baby prams), 1 considered the UFP levels in heavily trafficked streets, and 2 measured levels in homes . Two of the studies assessed exposure in more than one microenvironment …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations